On the origin of garden cemeteries in the West and references in the conformation of the first model in Brazil - Santos, Aline Silva (National Journal of City Management, 2023)
Garden cemeteries are found in many cities in Brazil and are an integral part of the system of urban open spaces and, therefore, fundamental elements in landscape planning, mainly due to their size. This article aims to investigate some of the first garden-cemetery models implemented in the West and the principles that were adopted in the first garden cemeteries built in Brazil. Using a systematic literature review, iconographic analysis, fieldwork and interviews, it was identified that one of the first garden cemeteries implanted in Brazil was the Cemitério da Paz, in São Paulo (SP), dating back to 1965, in which references were found mainly for lawn cemeteries and memorial parks in the USA from the mid-19th and early 20th centuries.